1997
DOI: 10.1093/glycob/7.8.1099
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and structural characterization of glycosphingolipids of in vitro propagated bovine aortic endothelial cells

Abstract: Neutral glycosphingolipids and gangliosides were isolated from 3.7 x 10 9 primary bovine aortic endothelial cells and structurally characterized by immunological and chemical methods. Glucosyl-and lactosylceramide were detected as the main neutral glycosphingolipids (28% and 40% of total orcinol stain, respectively); LcOse 3 Cer and nLcOse 4 Cer were expressed to somewhat minor amounts (16% and 10% of total orcinol stain, respectively), and nLcOse 6 Cer occurred only in trace quantities. No neutral glycosphing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 59 publications
2
29
0
Order By: Relevance
“…Glycosphingolipids, which all migrated in doublets, were identified by their comigration with standards on the HPTLC plates. We found that the major ganglioside of BRP and BREC was GM3 (71 and 81% of the total gangliosides, respectively), which agrees with the ganglioside composition of other vascular cells such as human umbilical vein endothelial cells and smooth muscle cells (22) or bovine aortic endothelial cells (23), where GM3 is the predominant ganglioside.…”
Section: Figsupporting
confidence: 82%
“…Glycosphingolipids, which all migrated in doublets, were identified by their comigration with standards on the HPTLC plates. We found that the major ganglioside of BRP and BREC was GM3 (71 and 81% of the total gangliosides, respectively), which agrees with the ganglioside composition of other vascular cells such as human umbilical vein endothelial cells and smooth muscle cells (22) or bovine aortic endothelial cells (23), where GM3 is the predominant ganglioside.…”
Section: Figsupporting
confidence: 82%
“…of ganglioside biosynthesis leads to a decreased capacity of endothelial cells to respond to FGF2. Endothelial cells express neuraminic acid-bearing GM 3 and GM 1 gangliosides (24,25). GM 1 binds FGF2 with a potency significantly higher than GM 3 (13).…”
Section: Resultsmentioning
confidence: 99%
“…The TTC fragment also displays gangliosides and p15-binding properties (11)(12)(13)(14)(15). Compared with neuronal tissues, b-type gangliosides are expressed less abundantly in skeletal muscle or endothelial cells (16,17), but that could explain binding and endocytosis into these cells. Gangliosides are known to segregate into membrane lipid microdomains called rafts and͞or caveolae, which contain high amounts of glycosphingolipids and cholesterol but also are enriched in a specific signaling molecule(s) (for reviews see refs.…”
Section: Discussionmentioning
confidence: 99%